Innovative activities of Ukraine in world ratings - Kobielieva, A. V. (Вінницький національний технічний університет, 2023)
A study of Ukrainit's place in global innovation ratings, such as the Global Innovation Index, European Innovation, European Innovation Scoreboard, and The Bloomberg innovation index, was conducted. The shortcomings and prospects of innovative development are determined, taking into account the current state of the Ukrainian economy.
Інноваційна діяльність України у світових рейтингах
Keywords: innovative development; indicators; ratings European perspectives